Developing a ball mill model that incorporates grate and overflow discharge configurations - Mwale, Adolph Ntaja (Department of Chemical Engineering, 2024)
The purpose of this thesis was to investigate performance differences between the grate and overflow discharge type ball mills of the same size under similar operating conditions using platreef ore which is classified as rheologically complex. The results from this investigation were used to develop a ball mill model that incorporates discharge mechanism and variables that influence mill power draw and product size distribution. Discharge configuration effects and power draw being one of the most important factors in ball mill performance, this thesis was set out to include these in performance prediction and analysis. The pilot ball mill operated by Magotteaux installed at the Anglo Platinum plant in Rustenburg was used to collect performance and operational data for use in the modelling. Two discharge configuration types were tested. The grate at two set open areas of 9.5% and 3.4% were used as well as the overflow type. The 1.25 m diameter and 2.20 m length mill was operated at two ball-load set points and a feed rate range of 1.50 tph to 2.25 tph for each configuration. Results showed that the grate configured ball mill produced much finer product compared to the overflow when operated under similar conditions. Results further showed that the grate ball mill had relatively higher breakage and discharge rates when operated at same conditions as the overflow. It was also shown that the grate discharge ball mill will draw an average of 18% more power than the overflow ball mill of the same size under similar operating conditions. Using these results, a new ball mill model was developed. The model is based on the principle that breakage distribution of the ore is unique to its competence and specific energy. The model incorporates mill operating conditions and retains the use of the appearance function. The model further incorporates influences of design and operating variable on mill power draw to predict product size distribution. It was found that the model agrees well with the pilot ball mill performance data. The model was later sub-developed into two models each specific to the discharge configuration type, the grate and overflow. For each configuration type, the model was found to give good predictions in agreement with real data. Thus, a model that considers the unique properties of the ore and discharge configuration incorporating mill power draw was developed.